Examining the association between public health unit spending and adolescent substance use - Urvi Rai; Karen A. Patte; Brendan T. Smith; Ambikaipakan Senthilselvan; Elaine Hyshka; Scott T. Leatherdale; Roman Pabayo (Heliyon)
Background: Based on the socio-ecological model of health, socioeconomic policy is an important determinant of population health. Spending decisions by public health units (PHU) have been shown to be associated with population health outcomes. Some studies have found greater PHU spending to be associated with improved population health, while others report mixed findings, warranting further research. The objective of this study was to investigate the association between per capita PHU spending and self-reported substance use among Canadian adolescents. Methods: Cross-sectional, multilevel modelling was conducted using student data from the 7th wave (2018/19) of the Cannabis use, Obesity, Mental health, Physical activity, Alcohol use, Smoking, and Sedentary behaviour (COMPASS) study, as well as spending data from the audited financial statements of Ontario's PHUs. The sample included 29,056 students in grades 9–12 attending 61 secondary schools in 15 PHUs across Ontario. Substance use was measured as the self-reported use of alcohol, cannabis, cigarettes and e-cigarettes, at least once per month on average. Results: Approximately 50 % of the study sample was female and the majority identified as being White. Per capita spending ranged from $54.07 to $224.95, with a median spending amount of $89.62. The highest quartile of PHU spending was significantly associated with higher alcohol use (adjusted odds ratio (AOR): 1.41, 95 % CI: 1.04, 1.91), binge drinking (AOR: 1.71, 95 % CI: 1.18, 2.48), and cigarette use (AOR: 2.19, 95 % CI: 1.23, 3.91) in adolescents, while the second highest quartile was associated with lower e-cigarette use (AOR: 0.74, 95 % CI: 0.56, 0.98), relative to the lowest quartile. Conclusion: Public health spending is associated with adolescent substance use. The present study reports mixed results, warranting further prospective research to explore the directions and mechanisms of the associations found.